A modified lambda algorithm for optimization in electromagnetics. Issue 3 (29th April 2014) - Alotto, Piergiorgio; dos Santos Coelho, Leandro; C. Mariani, Viviana; da C. Oliveira, Camila
Abstract : Purpose: – The purpose of this paper is to show with the help widely used analytical and application-oriented benchmark problems that a novel and relatively uncommon optimization method, lambda optimization, can be successfully applied to the solution of optimization problems in electromagnetics. Furthermore an improvement to the method is proposed and its effectiveness is validated. Design/methodology/approach: – An adaptive probability factor is used within the framework of lambda optimization. Findings: – It is shown that in the framework of lambda optimization (LO) the use of an adaptive probability factor can provide high-quality solutions with small standard deviation on the selected benchmark problem. Research limitations/implications: – Although the chosen benchmarks are considered to be representative of typical electromagnetic problems, different test cases may give less satisfactory results. Practical implications: – The proposed approach appears to be an efficient general purpose stochastic optimizer for electromagnetic design problems. Originality/value: – This paper introduces and validates the use of adaptive probability factor in order to improve the balance between the explorative and exploitative characteristics of the LO algorithm.